TINJAUAN YURIDIS TERHADAP PENYAMPAIAN INFORMASI PALSU YANG MEMBAHAYAKAN PENERBANGAN (ANALISIS PUTUSAN PN LABUHAN BAJO No. 43/Pid.B/2018/PN.Lbj) - Mugiran; Widarto, Bambang (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
Airplanes, which are the main means of transportation in aviation, actually have quite high risks in terms of safety and crime among passengers. One of the aviation crimes that often occurs is the case of spreading false information on airplanes, which currently often occurs is bomb jokes. Bomb jokes or bomb jokes made on board an airplane are actions carried out by a passenger by admitting that the person is carrying an object that could endanger the safety of other people even though that is not the case. This research is a Juridical Review of the Submission of False Information that Endangers Flights (Analysis of the District Court's Decision Labuhan Bajo No.43/Pid.B/2018/PN.Lbj). Problem Formulation 1. How is the regulation of criminal liability for perpetrators of criminal acts conveying false information that endangers aviation safety according to criminal law in Indonesia? 2. What are the legal considerations of the Panel of Judges in the decision of the Labuhan Bajo District Court No. 43/Pid.B/2018/PN.Lbj sentenced the defendant to the crime of conveying false information that endangered aviation safety? Research method This research uses a juridical-normative type of research by taking a statutory approach and a conceptual approach. Data collection from secondary materials was carried out using library methods and analyzed using qualitative methods. The results of this research are the regulation of perpetrators of criminal acts conveying false information that endangers aviation safety according to criminal law in Indonesia. In Article 437 point 1 it is stated that: